(untitled) - Young, George (Westport, Conn., 1985)
This book provides the non-technical reader with the insight and information necessary to understand those areas of the electronics industry that will be most affected by advances in electronic components and systems. The author reviews the general axioms of business and shows how and where they relate to the electronics industry. He examines new market opportunities brought about by changes in society and identifies fundamental trends which will affect future product and service offerings. The electronics industry, including the various steps in the production.
Keywords: Electronic industries,Venture capital,Công nghiệp điện tử,Vốn liên doanh; Finance,Tài chính